Implementation of Prophetic Value Education to Grow Early Literasi at Raudhatul Athfal (Case Study at RA Alam Gaharu School) - Masnipal Masnipal; Mubiar Agustin; Hilmy Azimah (Journal on Education, 2024)
This research aims to overcome the problem of low levels of early literacy in Raudhatul Athfal through the implementation of prophetic value education. The background to this research was sparked by concerns about the lack of attention to literacy development from an early age, which could affect children's reading and writing abilities in the future. The aim of this research is to evaluate the impact of implementing prophetic value education in increasing early literacy in the Raudhatul Athfal educational environment. The research method used is qualitative, with a case study approach to understand in depth the implementation and impact of prophetic value education. The research results show that this program has succeeded in increasing children's interest and involvement in literacy activities, as well as strengthening moral and ethical values. The conclusion of this research is that prophetic values ​​education can be effective in fostering early literacy in Raudhatul Athfal, emphasizing the importance of integrating moral values ​​in literacy learning from an early age. Therefore, it is suggested that this approach can be applied more widely in early education contexts to support children's holistic development.